Thickness distribution of multi-stage incremental forming with different forming stages and angle intervals - Li, Jun-chao; Yang, Fen-fen; Zhou, Zhi-qiang (Journal of Central South University, 2015)
Although multi-stage incremental sheet forming has always been adopted instead of single-stage forming to form parts with a steep wall angle or to achieve a high forming performance, it is largely dependent on empirical designs. In order to research multi-stage forming further, the effect of forming stages ( n ) and angle interval between the two adjacent stages (Δ α ) on thickness distribution was investigated. Firstly, a finite element method (FEM) model of multi-stage incremental forming was established and experimentally verified. Then, based on the proposed simulation model, different strategies were adopted to form a frustum of cone with wall angle of 30° to research the thickness distribution of multi-pass forming. It is proved that the minimum thickness increases largely and the variance of sheet thickness decreases significantly as the value of n grows. Further, with the increase of Δ α , the minimum thickness increases initially and then decreases, and the optimal thickness distribution is achieved with Δ α of 10°. Additionally, a formula is deduced to estimate the sheet thickness after multi-stage forming and proved to be effective. And the simulation results fit well with the experimental results.